Parental Involvement and Academic Performance of High School Students: A Correlational Study - N. Albiso, Christine Faith; R. Amante, Dhan Kenneth; H. Baruel, Angel Faith; Cabanilla, Angelito; D. Devilleres, Therese Rose; Thaddeus A. Dolino, Benedict Erm (International Journal of Humanities and Education Development (IJHED), 2022)
The main purpose of this study was to examine the correlation between parental involvement (PI) and academic performance (AP) among junior high school (JHS) students in selected schools in Cebu. This study employed a quantitative correlational design. There were thirty (30) JHS students who participated in this research who were identified using a simple random sampling method. Descriptive statistical tools, particularly mean and standard deviation were used to describe the level of PI and AP of the students. Consequently, the Pearson product-moment coefficient of correlation test was run to assess the correlation between PI and AP among JHS students. Based on the findings, it showed that there is a very low negative correlation between the two variables. Thus, there is no significant correlation between PI and AP among JHS students, r (30) = - .06, p = .74. With these results, the null hypothesis was not rejected since the p-value is greater than the significance level, p > .05. Therefore, PI does not affect the AP of the students. Findings suggest that educational staff and administrators be able to identify other factors that influence the AP of the students. Because the scope of this study is restricted within the perception of students towards PI, it would be better for the future studies to let the parents of the students be involved, and their side will be taken into consideration; new variables in the inquiry – motivation and self-competence among students; and to conduct a qualitative or a mixed-method study for future studies about the topic.